High Time Resolution Astrophysics - Phelan, Don.; Ryan, Oliver; Shearer, Andrew; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
High Time Resolution Astrophysics (HTRA) is an important new window to the universe and a vital tool in understanding a range of phenomena from diverse objects and radiative processes. This importance is demonstrated in this volume with the description of a number of topics in astrophysics, including quantum optics, cataclysmic variables, pulsars, X-ray binaries and stellar pulsations to name a few. Underlining this science foundation, technological developments in both instrumentation and detectors are described. These instruments and detectors combined cover a wide range of timescales and can measure fluxes, spectra and polarisation. These advances make it possible for HTRA to make a big contribution to our understanding of the Universe in the next decade.
High Time Resolution Astrophysics and Pulsars -- High Time Resolution Observations of Cataclysmic Variables -- High-Speed Optical Observations of X-ray Binaries -- Stellar Pulsation, Subdwarf B Stars and High Time Resolution Astrophysics -- High-Speed Optical Spectroscopy -- Photonic Astronomy and Quantum Optics -- ULTRACAM: An Ultra-Fast, Triple-Beam CCD Camera for High-Speed Astrophysics -- OPTIMA: A High Time Resolution Optical Photo-Polarimeter -- From QuantEYE to AquEYE-Instrumentation for Astrophysics on its Shortest Timescales -- Fast Spectroscopy and Imaging with the FORS2 HIT Mode -- An Ultra-High-Speed Stokes Polarimeter forAstronomy -- Use of an Extremely Large Telescope for HTRA -- EMCCD Technology in High Precision Photometry on Short Timescales -- The Development of Avalanche Amplifying pnCCDs: A Status Report -- Geiger-mode Avalanche Photodiodes for High Time Resolution Astrophysics -- Transition Edge Cameras for Fast Optical Spectrophotometry -- Imaging Photon Counting Detectors for High Time Resolution Astronomy.
Keywords: PHYSICS; WEIGHTS AND MEASURES; ASTRONOMY; ASTROPHYSICS; PHYSICS; ASTROPHYSICS; ASTRONOMY; ASTRONOMY, ASTROPHYSICS AND COSMOLOGY; MEASUREMENT SCIENCE, INSTRUMENTATION; EXTRATERRESTRIAL PHYSICS, SPACE SCIENCES